Urinary Schistosomiasis and Malaria -Associated Anaemia among Children in Dogo Community, Moro Local Government Area of Kwara State - Opalekunde, Ahmmed Bayo; Abdulrazaq, Nuhu; Adebayo, Nassar Sulaiman; Aminat, Ahmed; Bolanle, Ahmed Aishat; Mashood, Bolaji; Bolakale, Shuaib Abdulmumeen (Sahel Journal of Life Sciences FUDMA, 2025)
Urinary Schistosomiasis and malaria remain endemic in rural Nigerian communities, contributing significantly to the burden of anaemia among children. Despite control efforts, persistent co-infection and their impact on child health require localized investigation to inform effective interventions. This study investigates the prevalence of urinary schistosomiasis, malaria, their co-infection, and the relationship with anaemia among children aged 5–15 years in Dogo Community, Moro Local Government Area, Kwara State. One hundred children (47 males, 53 females) were randomly selected and screened. Urinary schistosomiasis was diagnosed via urine filtration microscopy detecting Schistosoma haematobium eggs, while malaria was identified through Giemsa-stained thin and thick blood smears targeting Plasmodium falciparum. Haemoglobin concentration was measured to assess anaemia status. Results reveal that 25% of participants tested positive for malaria, with females constituting 68%. Urinary schistosomiasis prevalence was 22%, predominantly among males (68.2%). Co-infection was detected in 5% of children, all males, who exhibited anaemia defined by haemoglobin levels below 11 g/dL. Notably, 37% of uninfected children maintained normal haemoglobin values, whereas the remainder had subnormal levels. Chi-square revealed a significant association between infection status and anaemia at 5% level of significance. These findings indicate that urinary schistosomiasis and malaria are significant contributors to anaemia and remain significant public health problems in the study area, with distinct gender disparities. The burden of co-infection and its link to anaemia underscore the urgent need for integrated control measures through mass drug administration, health education, and improved sanitation, to reduce the prevalence and impact of these diseases.